Kognitif Tuturan Tahanan Perempuan yang Mengalami Stres di Rumah Tahanan Kelas 1 Makassar - Ibrahim, Aprilyanti Nurna Nengsi; Nensilianti, Nensilianti; Sultan, Sultan (ppjbsip, 2025)
This study is a descriptive qualitative study that aims to (1) describe the cognitive form of speech of female prisoners experiencing mild stress in Makassar Class 1 Detention Center based on Ronald Langacker’s theory, (2) describe the cognitive pattern of speech of female prisoners experiencing moderate stress in Makassar Class 1 Detention Center based on Ronald Langacker’s theory, (3) describe the cognitive pattern of speech of female prisoners experiencing high stress based on Ronald Langacker’s theory. The focus of this study is on data in the form of words, phrases, clauses spoken by female prisoners experiencing mild stress, moderate stress and high stress. The data source for this study came from female prisoners in Makassar Class 1 Detention Center. Data collection techniques were carried out through observation, documentation and interviews. The research instruments consisted of the main instrument, namely the researcher and supporting instruments including observation guides, interview guides and recording devices. The results of the study showed that the cognitive pattern of speech of female prisoners experiencing mild stress was dominated by repetition patterns, especially repetition of phrases and ideas and emotional expression patterns in verbal and metaphorical forms. Meanwhile, the cognitive pattern of speech of female prisoners experiencing moderate stress was dominated by Ambiguity patterns, namely lexical and contextual, fragmentation patterns consisting of semantic and discourse fragmentation and more complex emotional expressions. Then, the cognitive pattern of speech of female prisoners experiencing high stress is dominated by a pattern of subject change, namely shifts in perspective and pronominal identity, syntactic and contextual ambiguity patterns, and structural fragmentation patterns.Abstrak Penelitian ini adalah penelitian kualitatif deskriptif yang bertujuan untuk (1) mendeskripsikan bentuk kognitif tuturan tahanan perempuan yang mengalami stres ringan di rumah tahanan kelas 1 Makassar berdasarkan teori Ronald Langacker, (2) mendeskripsikan pola kognitif tuturan tahanan perempuan yang mengalami stres sedang di rumah tahanan kelas 1 Makassar berdasarkan teori Ronald Langacker, (3) mendeskripsikan pola kognitif tuturan tahanan perempuan yang mengalami stres tinggi berdasarkan teori Ronald Langacker. Fokus penelitian ini yaitu pada data berupa kata, frasa, klausa yang dituturkan oleh tahanan perempuan yang mengalami stres ringan, stres sedang dan stres tinggi. Sumber data penelitian ini yaitu berasal dari tahanan perempuan di Rumah Tahanan kelas 1 Makassar. Teknik pengumpulan data dilakukan melalui observasi, dokumentasi dan wawancara. Instrumen penelitian terdiri dari instrumen utama yaitu peneliti dan instrumen pendukung meliputi panduan observasi, panduan wawancara dan alat perekam. Hasil penelitian menunjukkan bahwa pola kognitif tuturan tahanan perempuan yang mengalami stres ringan didominasi pola repetisi terutama repetisi frasa dan gagasan serta pola ekspresi emosional dalam bentuk verbal dan metaforis. Adapun pola kognitif tuturan tahanan perempuan yang mengalami stres sedang didominasi pola Ambiguitas yaitu leksikal dan kontekstual, pola fragmentasi terdiri dari fragmentasi semantik dan wacana serta ekspresi empsional yang lebih kompleks. Kemudian pola kognitif tuturan tahanan perempuan yang mengalami stres tinggi didominasi pola perubahan subjek yaitu pergeseran perspektif dan identitas pronominal, pola ambiguitas sintaksis dan kontekstual serta pola fragmentasi struktural.